Case Report: Trans-Articular External Skeletal Fixation of the Hip for a Highly Comminuted Juxta-Articular Fracture of the Proximal Femur Caused by Gunshot Injury in a Cat - Han, Hyun-Jung; Lee, Kyeongpung; Yoon, Hun-Young (Frontiers in Veterinary Science, 2021)
This report describes a novel surgical technique for trans-articular external skeletal fixation (TA-ESF) of the hip to stabilize a rare, highly comminuted juxta-articular fracture of the proximal femoral segment involving the metaphysis and diaphysis in a cat. A 2-year-old, castrated male, Korean shorthair cat was admitted for a left femoral fracture caused by gunshot injury. Radiographs and computed tomography (CT) scans revealed a highly comminuted proximal femoral diaphyseal fracture that involved the femoral neck and the greater trochanter. The left femoral head was intact on CT. Under fluoroscopic guidance, an intramedullary Steinmann pin was placed to align the femur, and five positive-profile, end-threaded pins were placed in the left hemipelvis and distal femur. A triangulated frame of connecting bars was constructed using Steinmann pins and epoxy resin for TA-ESF. This secured the pins placed in the pelvis and femur as well as the intramedullary pin, providing proximal femoral stabilization by trans-articular fixation of the hip. The cat began placing weight on the left pelvic limb 4 days postoperatively, and progressively obtained near-normal limb function by day 112. The TA-ESF was partially dismantled to a linear tie-in construct on day 64 and was completely removed on day 161. Final radiographs on day 161 revealed lack of bone healing in the proximal segment, especially femoral head and neck, despite functional recovery of the injured leg. At one year postoperatively, the cat had normal limb function without any noticeable complications. On follow-up 29 months after surgery, the owner reported that the cat had normal limb function without any noticeable complications. Despite insufficient bone healing in the cat, TA-ESF of the hip allowed for satisfactory functional recovery of this challenging juxta-articular fracture of the proximal femur, which was not amenable to stabilization with a traditional non-load-sharing fixation system.